1998
DOI: 10.2307/176818
|View full text |Cite|
|
Sign up to set email alerts
|

Ungulate vs. Landscape Control of Soil C and N Processes in Grasslands of Yellowstone National Park

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology. Abstract.Within large grassland ecosystems, climatic and topograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
247
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(267 citation statements)
references
References 54 publications
12
247
8
Order By: Relevance
“…Herbivores can change nitrogen input to the soil (Tracy and Frank 1998) and soil net nitrogen mineralisation (e.g. Holland et al 1992;Frank and Groffman 1998;Hamilton et al 1998), but the mineralisation rate is also strongly controlled by actual soil moisture (Holland et al 1992). Grazing can also affect the specific root uptake rate for nutrients (Ruess 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbivores can change nitrogen input to the soil (Tracy and Frank 1998) and soil net nitrogen mineralisation (e.g. Holland et al 1992;Frank and Groffman 1998;Hamilton et al 1998), but the mineralisation rate is also strongly controlled by actual soil moisture (Holland et al 1992). Grazing can also affect the specific root uptake rate for nutrients (Ruess 1984).…”
Section: Discussionmentioning
confidence: 99%
“…3. Accelerated or regulated nutrient recycling: plant growth may be stimulated by improved nutrient cycling induced by herbivory (Ruess 1984;Loreau 1995;McNaughton et al 1997;Frank and Groffman 1998;de Mazancourt et al 1999). 4.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated short term stimulations of denitrification rates following urine deposition (e.g. Monaghan and Barraclough 1993;de Klein and Logtestijn 1994;Fraser et al 1994; but see Frank and Groffman 1998b) and following defoliation events (Ruz-Jerez et al 1994;Luo et al 1999;). Increased denitrification rates at ecosystem-scale in response to long term (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies report the effects of insect outbreaks (Mattson and Addy 1975;Swank et al 1981), mega-herbivores (Pastor and Naiman 1992;Pastor et al 1993;Frank and Groffman 1998) or anthropogenic disturbances (Schowalter et al 1981), but it is less clear how endemic above-ground herbivory affects nutrient cycling and how it is related to below-ground soil chemistry. Seastedt et al (1983) found that low levels of consumption by canopy arthropods increased leaching of K + but not N from injured leaves.…”
Section: Introductionmentioning
confidence: 99%